PSYCHOANALYSIS, GROUP ANALYSIS AND BEYOND towards a new paradigm of the human being. - Tubert-Oklander, Juan. ([S.l.] : ROUTLEDGE, 2021)
Psychoanalysis, Group Analysis, and Beyond presents an important new paradigm in psychoanalysis and group analysis, presenting the individual and the group as elements of a wider whole and taking socio-political and cultural contexts into account. Juan Tubert-Oklander and Reyna Hernndez-Tubert explore the contributions of group analysis to this new perspective, which suggests a holistic conception of the respective status and nature of what the common-sense view of the world conceives as the individual and the community. Part I presents thoughts on the gelding' of psychoanalysis, focuses on the limitations of classical psychoanalysis, and elaborates on key topics including epistemology, inclusion and exclusion, culture, and the real. Part II considers the reincorporation of what had formerly been excluded, through the theory and practice of group analysis. Finally, Part III bridges the gap, presenting several approaches to the building of the new paradigm that is so sorely needed. Psychoanalysis, Group Analysis, and Beyond will be of great interest to group analysts, psychoanalysts, and psychotherapists in practice and in training, as well as other professionals specializing in group work.
Keywords: Psychoanalysis; Group psychoanalysis; Subconsciousness; PSYCHOLOGY / Movements / Psychoanalysis; PSYCHOLOGY / Mental Health